2002
DOI: 10.1111/j.1945-5100.2002.tb01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineral‐organic matter relationships in the early solar system

Abstract: Abstract-As the solar system formed, it inherited and perpetuated a rich organic chemistry, the molecular products of which are preserved in ancient extraterrestrial objects such as carbonaceous chondrites. These organic-rich meteorites provide a valuable and tangible record of the chemical steps taken towards the origin of life in the early solar system. Chondritic organic matter is present in the inorganic meteorite matrix which, in the CM and CI chondrites, contains evidence ofalteration by liquid water on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 17 publications
9
107
0
Order By: Relevance
“…It is found in the matrix of chondrites, associated with phyllosilicates (Pearson et al 2002). Organics likely accreted with other volatiles components in the matrix.…”
Section: How Did the Organics In Carbonacenous Chondrites Form?mentioning
confidence: 99%
“…It is found in the matrix of chondrites, associated with phyllosilicates (Pearson et al 2002). Organics likely accreted with other volatiles components in the matrix.…”
Section: How Did the Organics In Carbonacenous Chondrites Form?mentioning
confidence: 99%
“…This can be done at several scales. At the macroscopic scale, it appears that the organic matter is located in the matrix of chondrites, associated with phyllosilicates [81]. Osmium tetroxide vapour impregnation [84] labels specifically organic compounds in rocks and reveals that chondrules and CAIs are free of organic matter.…”
Section: Distribution Of the Iom: Understanding The Accretion Processmentioning
confidence: 99%
“…Location of organic matter in chondrites revealed by several techniques (the name of the corresponding meteorite is indicated into brackets). A and B: Osmium labelling reveals that organic matter occurs in the matrix, the chondrule being free of organic matter [81]. C: By fluorescence microscopy, organic matter (white structures) appear as isolated particles, with sizes ranging from 0.5 up to 4 microns randomly distributed in the matrix [82].…”
Section: Diversity Among the Different Types Of Chondrites: Influencementioning
confidence: 99%
“…The reduced CV also exhibit the same trend, though the range of D/H ratio is much smaller (a few hundred of permil compared to several thousands of permil in delta units). It must be EPOV 2012 03001-p. 5 noted that the lowest isotopic enrichment was measured in Abee enstatite chondrite (δD = -480 ‰; D/H = 80×10 -6 ) [56,57]. Isotopic imaging has revealed that H isotopes can exhibit large variations in the IOM of CI, CM and CR chondrites with the occurrence of D-rich " hot spots": micron sized areas with large positive D anomalies (figure 3), which could go up to δD = 8000 ‰ (D/H=1402×10 -6 ; [58][59][60]).…”
Section: Water In Chondritesmentioning
confidence: 99%
“…It is found in the matrix of chondrites, associated with phyllosilicates [5]. Organics likely accreted with other volatiles components in the matrix.…”
Section: Introductionmentioning
confidence: 99%